Preparation and characterization of undoped porous Gallium Nitride (GaN) by UV assisted electrochemical etching / Mohd Bukhari Md Yunus, Ainorkhilah Mahmood and Zainuriah Hassan. - Md Yunus, Mohd Bukhari; Mahmood, Ainorkhilah; Hassan, Zainuriah (2011)
lll-V nitride semiconductors such as GaN, InN and AIN and their alloys (AIGaN, InGaN, AlInGaN) have been investigated intensively in the last decade for their practical applications in short wavelength optoelectronic devices and high power/high frequency/high temperature electronic devices. These excellent applications are based on the unique and superior properties of nitride semiconductors such as wide direct band gap, strong piezoelectric effects (~0.2 - 0.6 GV/m), high-saturation velocity (-2.7x104 cm/s) and high breakdown field (-0.2x109 V/m) [1], A great deal of interest displayed in porous semiconductors in recent years is motivated by the prospects that they present in optoelectronics, chemical and biochemical sensors. The reduction of dimensions to nanometer sizes changes dramatically the physical properties of semiconductors and hence opens alternative possibilities for their applications. Porous semiconductors are also under study as possible templates for epitaxial growth where the pores might act as sinks for mismatch dislocations and accommodate elastic strain in heterostructures. The project proposed here is to prepare and study Ill-nitrides (GaN-based) porous structures. Various approaches such as electroless etching and other novel techniques will be investigated to prepare these nanoporous structures. Various characterization tools such as scanning electron microscopy (SEM), high resolution x-ray diffraction (HRXRD), photoluminescence and Raman spectroscopy will be used to investigate the structural and optical properties of the structures.